2017
DOI: 10.1111/pce.13010
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen isotope chronometer for cellulose deposition: the successive leaves formed by tillers of a C4 perennial grass

Abstract: Multiannual time series of (palaeo)hydrological information can be reconstructed from the oxygen isotope composition of cellulose (δ O ) in biological archives, for example, tree rings, but our ability to temporally resolve information at subannual scale is limited. We capitalized on the short and predictable leaf appearance interval (2.4 d) of a perennial C grass (Cleistogenes squarrosa), to assess its potential for providing highly time-resolved δ O records of vapour pressure deficit (VPD). Plants grown at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Following the procedure of Brendel et al (2000) as modified by Gaudinski et al (2005), α-cellulose was extracted from a subsample (50 or 25 mg) of ground plant material (for details see Liu et al, 2017b). After redrying of the cellulose at 80°C for 24 h, 0.7 mg aliquots were weighed into silver cups (size: 3.3 × 5 mm, IVA Analysentechnik e.K., Meerbusch, Germany) and stored above Silica Gel orange (2-5 mm, ThoMar OHG, Lütau, Germany) in exsiccator vessels.…”
Section: Cellulose Extraction and Isotopic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Following the procedure of Brendel et al (2000) as modified by Gaudinski et al (2005), α-cellulose was extracted from a subsample (50 or 25 mg) of ground plant material (for details see Liu et al, 2017b). After redrying of the cellulose at 80°C for 24 h, 0.7 mg aliquots were weighed into silver cups (size: 3.3 × 5 mm, IVA Analysentechnik e.K., Meerbusch, Germany) and stored above Silica Gel orange (2-5 mm, ThoMar OHG, Lütau, Germany) in exsiccator vessels.…”
Section: Cellulose Extraction and Isotopic Analysismentioning
confidence: 99%
“…Accordingly, the mean live leaf age (measured in growing-degree-days (GDD)) changes relatively little during the course of the vegetation period (Lemaire et al, 2000;Schleip et al, 2013). In a controlled environment study with Cleistogenes squarrosa (a perennial C 4 grass), Liu et al (2017b) found a close linear relationship between the fraction of remaining leaf elongation and the fraction of oxygen in cellulose assimilated following a change of RH in the growth environment, as inferred from 18 O-abundance measurements. Similar results were previously obtained by Helliker & Ehleringer (2002b), highlighting the potential of grass leaves as recorders of environmental signals in δ 18 O cellulose .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be inferred that the secondary cell wall probably contributes to the cell wall thickness, and hence to leaf width increase following cessation of longitudinal growth as seen in the C 3 monocotyledonous grass Festuca arundianacea Shreb 36,37 . As Liu et al 38 showed that α‐cellulose (a major component of cell wall) deposition stopped at (or shortly after) full leaf expansion in a perennial C 4 monocotyledonous grass Cleistogenes squarrosa , it can also be inferred that the hemicellulose is probably the dominant component of the secondary wall.…”
Section: Resultsmentioning
confidence: 96%
“…α-Cellulose, a linear polymer of β(1 → 4) linked d -glucose, is not only abundant but is also chemically and isotopically stable over geological time. These properties make α-cellulose the preferred plant material from which oxygen isotope ratios ( 18 O/ 16 O) can be extracted for climate, environmental, and physiological and metabolic studies. , As a single component, the use of α-cellulose 18 O/ 16 O ratios avoids the biases due to the existence of isotopically different components in variable portions in bulk plant materials . However, reliable application of such ratios is dependent on obtaining acceptably pure products, as evidence is accumulating that hemicellulose-derived non-glucose sugars and lignin (a three-dimensional (3D) heterogeneous polymer of phenylpropanoids), the two major oxygen-containing impurities frequently found in α-cellulose products, are isotopically different from that of the d -glucosyl units derived from α-cellulose. Note that throughout this paper, α-cellulose refers to the theoretically pure homopolymer of d -glucose, while α-cellulose product refers to impurity-containing α-cellulose extracted from plant materials.…”
mentioning
confidence: 99%